The Model for The Productivity towards Operation Facilities affecting Operation Performance of Industrial Entrepreneurs (SMI) in Phetchabun ProvinceThe Model for The Productivity towards Operation Facilities affecting Operation Performance of Industrial E - Khowjoy, Kritchai (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
This research aim to studied the operation facilities, and productivity which influenced of the operation performance in the cost and delivery aspects of Thai industrial entrepreneurs. The population was SME entrepreneurs in the manufacturing industry in Phetchabun who registered for the government’s reorganization project. The research used 259 questionnaires to collect data. Researcher collected data with purposive sampling. Statistical analysis used structural equation model analysis. The research results showed that (1) the research model was consistent with empirical data (Chi-square/df = 1.697, GFI = 0.919, CFI = 0.906, IFI = 0.909, RMR = 0.086, RMSEA = 0.052), (2) the operation facilities in technology aspect had a significant, positive direct influence on the labor productivity, and (3) the operation facilities in technology aspect had a significant, positive indirect influence on operation performance both cost and delivery aspects through the labor productivity. This research suggests that industrial entrepreneurs should focus on improve the operation facilities in technology aspect for increase the labor productivity which is a major influence on the cost and delivery.